A Techno-Efficiency Analysis of Zakat Institutions in Indonesia - Nikmatul Atiya; Tika Widiastuti; Eko Fajar Cahyono; Siti Zulaikha; Imron Mawardi (Center of Strategic Studies (PUSKAS) BAZNAS, 2020)
Zakat institutions play an important role in managing zakat effectively and efficiently as described in Law no. 23 of year 2011. This study aims to analyze the efficiency of zakat institutions in Indonesia and determine the best ranking of the units observed. This study uses a descriptive quantitative approach with the Super Efficiency Analysis. The study objects are BAZNAS, Rumah Zakat, Dompet Dhuafa, and YBM PLN with the 2016-2018 observation period. Personnel costs, operational costs, and socialization costs are input variables. While the output variables used are the amount of zakat collected and the amount of zakat distributed. The results of super-efficiency measurement show that the 3 best DMU rankings were achieved by YBM PLN 2016, BAZNAS 2018 and BAZNAS 2017. While the other 9 DMUs were inefficient. Inefficiency is due to the not optimal amount of zakat collected and zakat distributed and the high use of socialization costs. The variable of the amount of zakat collected is the most sensitive variable to the value of efficiency. To achieve performance efficiency, technology can be utilized to improve input and output. This research can be used as an evaluation material for zakat institutions to optimize efficiency. Keywords: Super Efficiency; Zakat Institution; Technology